Prácticas de enseñanza de las matemáticas en educación general básica :análisis de caso en segundo año en la escuela de educación básica Dr. Camilo Gallegos Toledo - Latacunga Pastuña, María Dora (2016)
About the theme “Practices of Mathematics teaching in Ecuador”, there is not any document either an analys of it. Some searches have been carried out in thesis of degrees and masteries have not found any reference on this subject. Therefore, this case study raised in the context of the Unit for Special Degree from the “Salesian Polytechnic University”, Department of Education, in the Race of Intercultural Bilingual Education, sought to observe and describe teaching practice in the classroom in the area math, second year in the categories of the curriculum, such as structure: planning, implementation of teaching and learning, work organization of the learning experience, interaction teacher-student activities learning experience, strategies evaluation and type of academic tasks. It also presents key findings, organized from data obtained from direct observation of classes, collected in the field diary, record of classroom observation and teacher interview. As one of the fundamental aspects, describes the results of the phenomena occurring in the practices in the classroom, the results showed the non-use planning, motivation is not in keeping with the theme of class among others. For their support has a theoretical foundation that highlights the following topics: teaching practices mathematics curriculum conceptions of class structure; analysis and presentation of results, conclusions and bibliography.